The involvement of Antifreeze protein maxi-like and Cold-shock domain-containing protein genes in cold-induced larval diapause and cold-shock treatment of khapra beetle. (March 2023) - Dageri, Asli; Kadir, Mohammed Lengichow; Guz, Nurper; Ogreten, Ayhan; Arshad, Muhammad
Abstract: The khapra beetle, Trogoderma granarium (Everts) (Coleoptera: Dermestideae), is a cosmopolitan and one of the most destructive pests of various stored grains and grain products. This pest is categorized as a quarantine threat in many countries. The larvae undergo diapause that lasts for several years depending on different stress conditions such as temperature, insecticidal applications, starvation, humidity, crowding, and fecal pellets. When conditions are favorable for the development, diapause terminates and the larva continues its development. In the present study, two cold-regulated genes Antifreeze protein maxi-like ( TgAFP ) and Cold-shock domain-containing protein E1 ( TgCSDP ) were identified in the cDNA library of T. granarium . Nucleotide sequences of two unigene cDNAs encoding TgAFP and TgCSDP were verified using RT-PCR and RACE-PCR amplifications. Transcriptional regulations of TgAFP and TgCSDP were examined in cold-induced diapause larvae, cold-shocked larvae, and at different developmental stages. Gene expression pattern of TgAFP revealed the highest mRNA levels during pre-diapause (25 °C) followed by the larvae exposed to 5 °C during the diapause phase. This can be attributable to the protective role of TgAFP against temperature fall. Significant upregulation of TgCSDP at 15 °C might indicate its probable chaperone role in toleration for cold-induced diapause. TgAFP level was downregulated after cold-shock treatment (CST), while it was slightly upregulated by recovery, indicating that it might confer tolerance for the recovery period (RP). The highest TgCSDP expression after the CST might suggest its involvement in response to acute CST. Low abundance of TgAFP expression in each developmental stage might suggest that 33 °C temperature does not induce the synthesis of TgAFP . Significant amount of TgCSDP levels in adults might indicate its putative role in development. These findings suggest that TgAFP and TgCSDP genes might be crucial for cold survival where the T. granarium undergoes its facultative diapause. Highlights: TgAFP s started to be remarkably expressed in pre-diapause larvae of Trogoderma granarium. Expression levels of TgCSDP reached a peak at 15 °C in diapause larvae of Trogoderma granarium. TgAFP was downregulated after cold-shock treatment and it was slightly upregulated by recovery. Cold-shock treatment caused a significant upregulation on TgCSDP at first half hour.